Projection of upwelling-favorable winds in the Peruvian upwelling system under the RCP8.5 scenario using a high-resolution regional model - Chamorro A. (2021)
The Peruvian upwelling system (PUS) is the most productive Eastern Boundary Upwelling System (EBUS) of the world ocean. Contrarily to higher latitude EBUSs, there is no consensus yet on the response of upwelling-favorable winds to regional climate change in this region. Global climate models are not able to reproduce the nearshore surface winds, and only a few downscaling studies have been performed by using relatively coarse-grid atmospheric models forced by idealized climate change scenarios. In the present study, the impact of climate change on the PUS upwelling-favorable winds was assessed using a high resolution regional atmospheric model to dynamically downscale the multi-model mean projection of an ensemble of 31 CMIP5 global models under the RCP8.5 worst-case climate scenario. We performed a 10-year retrospective simulation (1994–2003) forced by NCEP2 reanalysis data and a 10-year climate change simulation forced by a climate change forcing (i.e. differences between monthly-mean climatologies for 2080–2100 and 1989–2009) from CMIP5 ensemble added to NCEP2 data. We found that changes in the mean upwelling-favorable winds are weak (less than 0.2 m s?1). Seasonally, summer winds weakly decrease (by 0–5%) whereas winter winds weakly increase (by 0–10%), thus slightly reinforcing the seasonal cycle. A momentum balance shows that the wind changes are mainly driven by the alongshore pressure gradient, except in a local area north of the Paracas peninsula, downstream the main upwelling center, where wind increase in winter is driven by the shoreward advection of offshore momentum. Sensitivity experiments show that the north–south sea surface temperature gradient plays an important role in the wind response along the north and central coasts, superimposed onto the South Pacific Anticyclone large-scale forcing. A reduction (increase) of the gradient induces a wind weakening (strengthening) up to 15% (25%) off the northern coast during summer. This local mechanism is not well represented in global climate models projections, which underlines the strong need for dynamical downscaling of coastal wind in order to study the impact of climate change on the Peruvian upwelling ecosystem. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.